NEOROCKS project: surface properties of small near-Earth asteroids. Issue 2 (31st January 2023) - Hromakina, T; Birlan, M; Barucci, M A; Fulchignoni, M; Colas, F; Fornasier, S; Merlin, F; Sonka, A; Anghel, S; Poggiali, G; Belskaya, I; Perna, D; et al.
ABSTRACT: We present new results of the observing program which is a part of the NEOROCKS project aimed to improve knowledge on physical properties of near-Earth Objects (NEOs) for planetary defense. Photometric observations were performed using the 1.2-m telescope at the Haute-Provence observatory (France) in the BVRI filters of the Johnson–Cousins photometric systems between June 2021 and April 2022. We obtained new surface colours for 42 NEOs. Based on the measured colours, we classified 20 objects as S-complex, nine as C-complex, nine as X-complex, two as D-type, one object as V-type, and one object remained unclassified. For all the observed objects, we estimated their absolute magnitudes and diameters. Combining these new observations with the previously acquired data within the NEOROCKS project extended our data set to 93 objects. The majority of objects in the data set with diameters D < 500 m belongs to a group of silicate bodies, which could be related to observational bias. Based on MOID and Δ V values we selected 14 objects that could be accessible by a spacecraft. Notably, we find D-type asteroid (163014) 2001 UA5 and A-type asteroid 2017 SE19 to be of particular interest as possible space mission targets.